The Impact of EPS, PER, CR, and ROE on the Sharia Share Prices on the Indonesia Stock Exchange - Umardilopa, Jevi Azi; Projo, Nucke Widowati Kusumo (Al-Muamalat: Jurnal Ekonomi Syariah, 2025)
The public's need for Sharia investment is also increasing along with an increase in the number of Muslim populations. From 2019 to 2023, the total number of Sharia stock firms on the Indonesia Stock Exchange (IDX) has consistently remained stable or increased, without any decline. Behind these prospects, Sharia companies show quite volatile stock price movements. Therefore, a financial ratio analysis needs to be carried out. Financial ratios such as Earnings per Share (EPS), Price to Earnings Ratio (PER), Current Ratio (CR), and Return on Equity (ROE) are useful for assessing a company's valuation. Novelty in this paper is the integration of Sharia principles with financial ratios to assess the condition of Sharia companies. This study aims to analyze the effect of EPS, PER, CR, and ROE on the Sharia stock price. The research utilized secondary data from the second trimester of 2023 obtained from the IDX. The research methods are analysis descriptive and inferential analysis using robust regression. This research shows that EPS variable, PER variable, and ROE variable have a positive and significant impact on Sharia share prices, meanwhile CR has no significant effect and has a negative direction on the stock prices of Sharia company. Therefore, investors need to consider the EPS value, PER, and ROE before making investment decisions. This study's findings could be utilized by investment organizations to identify important factors affecting stock prices therefore potential investors may use it as guidance to get optimal profit.